Strategi Optimalisasi Produksi Gula Menggunakan Pendekatan Linear Programming di PT PG Candi Baru Sidoarjo - Achmad Misbah; Syahril Kirom, Muhammad Alfan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
his study aims to develop a strategy to optimize sugar production at PT PG Candi Baru Sidoarjo by utilizing a linear programming approach as a decision analysis tool. By modeling the system using POM-QM for Windows software, results indicate the potential for a 10–20% increase in production without requiring additional investment. This model provides a more objective basis for decisions and identifies capacity constraints that require attention. These findings are expected to assist management in improving operational efficiency and company competitiveness.